Reveal The Bugis Culture Of MSME Tax Compliance In Maros District In The New Normal Era - Nadiah, Khaerun; Bulutoding, Lince; Jannah, Raodahtul (Politeknik Keuangan Negara STAN, 2023)
This research is motivated by the phenomenon of community disobedience, especially MSME actors in carrying out their tax obligations. This study aims to examine the role of local wisdom, namely the culture of adaâ€™tongeng, lempu, getteng and pamali which is a new form of innovation in supporting the tax compliance of MSME actors. In order to explore the tax compliance of MSME actors from the perspective of local culture, phenomenology is used as a methodology with an interpretive paradigm as an umbrella of research. In carrying out tax obligations there are Buginese values called interpreted and in the application, which in this study tax compliance there is ada tongeng, lempu, getteng a short get at TKPALG. Pamali culture has not been implemented so that pamali culture is only knowledge. Â